The influence of numerical variability in small-sided games on youth football goalkeepers’ tactical-technical behaviour - Sousa, Honorato (2022)
Purpose. The main purpose of this study was to investigate changes in the tactical-technical behaviour of football goal keepers (GKs) across 5 small-sided games (SSGs) formats with temporary numerical variability. Methods. The sample involved 4 male under-17 GKs from the same team aged 16.1 ± 0.52 years. Three sessions were held on 3 different days to collect information. On each day, the 10-minute SSGs exercise with temporary numerical vari ability was repeated twice. The numerical ratio of players changed every 2 minutes without interrupting the practice. The exercise always started with a situation of 3 vs. 3 + GK (‘+ GK’ for both teams in each format), going through 4 vs. 3 + GK, 5 vs. 3 + GK, 3 vs. 4 + GK, and 3 vs. 5 + GK. Results. The 3 vs. 3 + GK format and the numeric superiority by 1 and 2 (4 vs. 3 + GK and 5 vs. 3 + GK) induced fewer defensive tasks in comparison with numeric inferiority (3 vs. 4 + GK and 3 vs. 5 + GK). From an offensive perspective, 3 vs. 3 + GK caused more offensive tasks in comparison with numeric superiority by 1 and 2 (4 vs. 3 + GK and 5 vs. 3 + GK). However, the game formats in numeric inferiority (3 vs. 4 + GK and 3 vs. 5 + GK) induced more offensive tasks. Conclusions. This study suggests the use of temporary numerical variability SSGs to increase offensive and defensive GK tactical-technical behaviour.